1994
DOI: 10.1080/00071669408417725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary energy restriction on retention of protein, fat and energy in broiler chickens

Abstract: 1. Broiler chickens were fed 60-100% of recommended energy intakes to study the effects of energy restriction on protein and fat retention. 2. At an energy retention of 179 kJ/kg W0.75 d, only protein was retained. At higher energy intakes, each increment in retention had a rather constant composition: about 85% energy in fat and 15% in protein. At lower energy intakes body fat was mobilised whereas protein was deposited. 3. The efficiencies of energy retention in protein and fat were estimated to be 0.66 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 13 publications
7
32
0
11
Order By: Relevance
“…Thus, the lower the dietary energy: protein ratio, the leaner the carcass. This find is consistent with Summers et al (1992) and Boekholt et al (1994), who also found a reduction in fat deposition due to a decrease in dietary energy: protein ratio.…”
Section: Carcass Parts Viscera and Abdominal Fat Yieldssupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, the lower the dietary energy: protein ratio, the leaner the carcass. This find is consistent with Summers et al (1992) and Boekholt et al (1994), who also found a reduction in fat deposition due to a decrease in dietary energy: protein ratio.…”
Section: Carcass Parts Viscera and Abdominal Fat Yieldssupporting
confidence: 81%
“…The fact that higher energy consumption promotes better weight gain is well established (Boekholt et al, 1994;Lesson et al, 1996); however, why dietary energy level does not affect broiler feed intake in some cases remains unanswered. In fact, the nutritional factors involved in broiler feed intake control mechanisms are not completely understood, and seemingly other macronutrients than energy influence feed behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a trend was not found in the native birds, however (Table 6). Metabolizable energy intake affects BW and composition (Boekholt et al, 1994;Wiseman and Lewis, 1998). Geneticists have selected broilers for many years to grow faster and achieve a bigger size sooner (Havenstein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The energy retained in the body as protein and lipid can be quantified based on their heats of combustion, i.e. 23.8 and 39.6 MJ kg −1 , respectively (Boekholt et al 1994;Emmans 1994). These combustion heat values vary slightly throughout literature, probably due to differences in the proportions of the components on which the average properties are determined; however, it cannot be expected that the chemical structure of proteins and lipids (and therefore their combustion heat values) could be altered via artificial selection and so these values were kept constant in our calculations.…”
Section: Quantitative Assessment Of Genetic Change In Broiler Energy mentioning
confidence: 99%